MODEL MATEMATIKA EKSTRAKSI COFFEE OIL DARI LIMBAH AMPAS KOPI BERDASARKAN PERBEDAAN TEMPERATUR - Mega Mustikaningrum; Rara Ayu Lestary; Nita Widyastuti; Fikrah Dian Indrawati Sawali (Program Studi Teknik Kimia, Universitas Pamulang, 2025)
In the past decade, coffee productivity, particularly instant coffee production, has experienced significant growth. This increase has generated more coffee grounds as a by-product, which is now widely utilized in the cosmetics and energy sectors, especially for producing coffee oil. Optimization of coffee oil isolation methods continues to be developed to improve efficiency. This study aims to obtain optimal values for the coffee oil diffusivity parameter (Da) and extraction rate constant (k). Coffee grounds extraction was performed using Hexane solvent with the aid of ultrasonic waves through a bath-type sonicator. The research was conducted with variations in temperature (30°C and 40°C) and extraction time (30, 60, 90, and 120 minutes). The research results showed that the coffee oil diffusivity values at temperatures of 30°C and 40°C were 9.93 x 10⁻¹⁰ and 9.99 x 10⁻¹⁰ dm²/s, respectively. The extraction rate constants obtained at each temperature were 0.450 and 0.667 dm/s.